Cultural Analysis of the Arabic Language Textbooks of Muhammadiyah Elementary School - Annafiri, Ahmad Zaki; Suseno, Andi; Azizah, Ilmah Fitrotul; El Kafoor, Ahmad Mizaj; Azzahro, Firda Saphira (IAIN Madura, 2024)
Culture is an important aspect of language. In the case of language textbooks, culture has an important role in conveying values to student learners. The objectives of this research are: 1) Describe the elements of Culture according to Keontjaraningrat; 2) Describe the cultural elements in Arabic books for Muhammadiyah elementary schools. The research method used was document analysis of Muhammadiyah Elementary School Arabic language textbooks for grades 4, 5 and 6, using Koentjaraningrat's cultural elements approach. The results of this research show that Koenjtaraningrat's seven cultural elements, namely religious systems and religious ceremonies, social systems and organizations, knowledge systems, language, art, livelihoods, and technological equipment systems are in the Muhammadiyah Elementary School Arabic language textbooks for grades 4, 5, and 6. Specifically for religious systems, the author provides the largest portion of the book's contents, marked by the mention of verses from the Koran and hadith at the beginning of each theme, the names of the characters used, pictures of people wearing Islamic clothing, as well as instilling morals contained in conversational texts.